Odpowiedzi

2010-01-27T18:06:16+01:00
1)a+2b+3c-4c-5b-6a=-5a-c
2)a³+2a-a²+3a²-10a³+5= -9a³+2a² +2a +5
3)5x²-x²+y²+y-3-y+(-2)y²+5=4x² -y² +2
4)13x+7y-10x-4y+5y=3x +8y
5)90x+3y-x²-9*9x-2y+x²= 9x+y
Najlepsza Odpowiedź!
2010-01-27T18:07:22+01:00
A) = -5a - 3b - c
b)= -10a³ + 2a - 2a² +5
c) = 4x² - 2y² - 2
d) = 3x + 8y
e) = 9x + y
2010-01-27T18:20:21+01:00
1)a+2b+3c-4c-5b-6a= -5a-3b-c
2)a³+2a-a²+3a²-10a³+5= -9a3+2a+2a2+5
3)5x²-x²+y²+y-3-y+(-2)y²+5= 4x2 -y2+2
4)13x+7y-10x-4y+5y=3x+8y
5)90x+3y-x²-9*9x-2y+x²=9x+y